Control strategies for microgrid with multiple distributed energy resources - Rahman, Sumaiya (2015)
Microgrid is considered as a smart solution to the global energy crisis and environmental issues these days for employing green technology. This is a small scale, usually renewable energy based distributed generation system which basically serves local users and does not require transmission lines. However, Microgrid needs a suitable control system to improve its efficiency and reliability to work as a standalone unit or as parallel connected unit with the main utility grid. For instance, renewable energy sources such as, Solar Photovoltaics and Wind Turbine depend on weather conditions thus result in output power fluctuation. In this case, a storage unit is essential that can provide back up during low generation period and can store outstanding energy at the time of less demand. In addition, integration of multiple distribution energy resources raises the energy generation of Microgrid sufficiently but increases complications in operations as well. Besides, a communication network is also vital in this case for information transfer within the sources and other components of the structure. Hence, a study related to advance control system to maintain a smart energy management incorporation with fault detection and self-healing aspects of Microgrid is presented in this research. The purpose of this project is to find out the most advantageous control techniques for Microgrid with multiple distributed energy resources which need to be user-friendly as well. Research shows that, Droop control techniques are beneficial for above requirements performing Decentralized control method where communication networks are not essential. Moreover, in this paper some MATLAB/SIMULINK based simulations are presented. Where a Microgrid is modelled that consists of distributed energy resources namely Photovoltaic, Wind turbine and Fuel cells. Finally, simulation results of different droop control techniques are presented and some discussions regarding tested techniques are enclosed.